PEMETAAN PREFERENSI KONSUMEN SUPERMARKET DENGAN METODE KANO BERDASARKAN DIMENSI SERVQUAL - Kriswanto Widiawan; Irianty Irianty (Institute of Research and Community Outreach - Petra Christian University, 2004)
The management of supermarket usually has some assumptions about the customers' expectation. Sometimes these assumtions do not reflect the nature of customers' expectations. Because of this miss perception, the supermarket looses its profit and becomes inefficient. This research was carried out in order to find out the customers' expectation on facilities and services of the supermarkets according to the servqual dimensions. The outcomes will be mapped into Kano categorizations. The researcher asked the customer dan manager of four supermarkets to fill the prepared questionnaires. Based on the result of customers' questionnaires, tangible, reliability and assurance dimensions were categorized as one dimensional. While responsiveness and emphaty dimensions were categorized as indifferent. Based on the result of managers' questionnaires, all servqual dimensions were categorized as one dimensional. After comparing the results of customers' and managers' questionnaires, there are three of four supermarkets which are match each other. Abstract in Bahasa Indonesia : Manajemen supermarket pada umumnya memiliki asumsi-asumsi mengenai harapan konsumen yang belum tentu sama dengan harapan konsumen sesungguhnya. Akibat ketidaktahuan informasi penting tersebut, tidak sedikit supermarket yang mengalami kerugian atau kinerjanya tidak efisien. Tujuan penelitian ini adalah mengetahui harapan konsumen tentang fasilitas dan layanan supermarket menurut dimensi servqual yang dipetakan ke dalam kategori Kano. Penelitian dilakukan terhadap konsumen dan manajer dengan cara memberikan kuesioner. Menurut responden konsumen supermarket, dimensi servqual yang tergolong kategori one dimensional adalah tangible, reliability dan assurance. Sedangkan dimensi responsiveness dan emphaty termasuk kategori indifferent. Sementara itu, responden manajer supermarket berpendapat semua dimensi servqual termasuk kategori one dimensional. Dari empat supermarket yang diteliti, diketahui ada tiga supermarket yang cocok persepsinya antara manajer dengan konsumennya. Kata kunci: Dimensi servqual, metode Kano, kepuasan konsumen.